Chinese herbal medicine for hypertension complicated with hyperlipidemia: A protocol for a systematic review and meta-analysis. Issue 6 (12th February 2021) - Liu, Yinan; Liu, Yiqing; Yang, Jing; Wang, Xue; Xiu, Chengkui; Hu, Yanhong; Wu, Dan; Wu, Ye; Lei, Yan
Abstract: Background: Hypertension combined with hyperlipidemia (HTN-HLP), as a common clinical chronic disease combination, will increase the incidence of cardiovascular and cerebrovascular diseases, increase the occurrence of sudden death and other adverse events. At present, the commonly used therapeutic drugs are mainly combined with antihypertensive drugs and lipid-lowering drugs, which not only have poor compliance, but also have adverse reactions. Currently, traditional Chinese medicine, as a traditional medicine in China, has been applied in clinical practice for thousands of years and has rich clinical experience in treating HTN-HLP. However, there is no systematic evaluation of the efficacy, safety and improvement of patients' quality of life. This systematic review and meta-analysis will assess studies of the effects and safety of Chinese herbal medicine (CHM) for HTN-HLP patients. Methods: We will search PubMed, Embase, Cochrane Central Register of Controlled Trials, Web of Science (ISI), China National Knowledge Infrastructure, Wan fang Database, Chinese Scientific Journals Full-Text Database (VIP) and China Biological Medicine Database from the time when databases were established to 01, February 2021. After a series of screening, randomized controlled trials (RCTs) will be included related to CHM for HTN-HLP. Two researchers will assess the RCTs through the Cochrane bias risk assessment tool. And the evidence grade of the results will be evaluated by GRADEprofiler software. Results: This study will provide a reliable evidence for the efficiency of antihypertensive and reducing blood lipids of CHM for HTN-HLP. Conclusion: We will summarize the methods and provide sufficient evidence to confirm the efficacy and safety of CHM for HTN-HLP. INPLASY registration number: INPLASY2020110144. Abstract : Supplemental Digital Content is available in the text